The Maslahah Hajiyah Perspective of Sharia Economic Law on Women Working Night Shifts - Annisa Salsabila; Dessy Asnita; Ryzka Dwi Kurnia; Asih Pertiwi; Agustinar Agustinar (Fakultas Syariah Universitas Islam Negeri Sultanah Nahrasiyah Lhokseumawe, 2025)
The phenomenon of women working night shifts in Langsa City is increasing, in line with economic needs and the flexibility of time offered. This job is often considered a solution for women to contribute to the family economy without abandoning their family responsibilities. However, night work also brings various challenges such as health problems, stress, and impacts on social interactions and time with family. This study aims to analyze the factors that encourage women to work night shifts in Langsa City and assess these practices from the perspective of maslahah hajiyah in Islamic law. This research uses a qualitative descriptive method with an empirical juridical approach. Data was obtained through observation, interviews, and documentation. Interviews were conducted with women working night shifts in sectors such as restaurants, shops, and health facilities. The results of the study show that economic factors, family responsibilities, and time flexibility are the main motivations for women to work at night. From the perspective of maslahah, night work for women can be considered maslahah hajiyah, which is a secondary need to improve the economic welfare of the family, as long as the work is halal and does not cause greater harm. These findings contribute to the discourse on women's empowerment and the application of Sharia principles in the context of night work for women.